Identifying individuals with opioid use disorder: Validity of International Classification of Diseases diagnostic codes for opioid use, dependence and abuse. (1st April 2021) - Lagisetty, Pooja; Garpestad, Claire; Larkin, Angela; Macleod, Colin; Antoku, Derek; Slat, Stephanie; Thomas, Jennifer; Powell, Victoria; Bohnert, Amy S.B.; Lin, Lewei A.
Highlights: Opioid-related diagnosis codes are used to identify opioid use disorder (OUD). But it is unclear how accurately these codes map onto standard criteria for OUD. We reviewed patients' medical records for evidence of an OUD in the clinical notes. Over 40 % of patients with opioid-related diagnosis codes did not meet OUD criteria. There is a need for more robust methods of identifying individuals with OUD. Abstract: Background: Policy evaluations and health system interventions often utilize International Classification of Diseases (ICD) codes of opioid use, dependence, and abuse to identify individuals with opioid use disorder (OUD) and assess receipt of evidence-based treatments. However, ICD codes may not map directly onto the Diagnostic and Statistical Manual of Mental Disorder (DSM-5) OUD criteria. This study investigates the positive predictive value of ICD codes in identifying patients with OUD. Methods: We conducted a clinical chart review on a national sample of 520 Veterans assigned ICD-9 or ICD-10 codes for opioid use, dependence, or abuse from 2012 to 2017. We extracted evidence of DSM-5 OUD criteria and opioid misuse from clinical documentation in the month preceding and three months following initial ICD code listing, and categorized patients into: 1) high likelihood of OUD, 2) limited aberrant opioid use, 3) prescribed opioid use without evidence of aberrant use, and 4) insufficient information. Positive predictive value was calculated as the percentage of individuals with these ICD codes meeting high likelihood of OUD criteria upon chart review. Results: Only 57.7 % of patients were categorized as high likelihood of OUD; 16.5 % were categorized as limited aberrant opioid use, 18.9 % prescribed opioid use without evidence of aberrant use, and 6.9 % insufficient information. Conclusions: Patients assigned ICD codes for opioid use, dependence, or abuse often lack documentation of meeting OUD criteria. Many receive long-term opioid therapy for chronic pain without evidence of misuse. Robust methods of identifying individuals with OUD are crucial to improving access to clinically appropriate treatment.